2018
DOI: 10.1177/1933719117718274
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Levonorgestrel-Releasing Intrauterine System Insertion After Gonadotropin-Releasing Hormone Agonist Treatment for Preventing Endometriotic Cyst Recurrence: A Prospective Observational Study

Abstract: The aim of this study was to evaluate the effectiveness of postoperative levonorgestrel-releasing intrauterine system (LNG-IUS) insertion after gonadotropin-releasing hormone agonist (GnRH-a) treatment for preventing endometriotic cyst recurrence. Study Design: The LNG-IUS was applied to 28 women who had undergone surgery for endometriosis followed by 6 cycles of GnRH-a treatment. Clinical characteristics, endometriosis recurrence, and adverse effects were analyzed. Student t test was performed for analysis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…There was a significant decrease in the recurrence rate of dysmenorrhea (P¼ .019) and significant reduction in the mean dysmenorrhea VAS score when compared with non-users. Additionally, a significant improvement in the VAS pain score (baseline 4.26 vs. 0.50, P< .0001) was reported among 28 patients after laparoscopic surgery for endometriosis followed up for 3 years after placement of the LNG-IUS (26). The bleeding patterns reported in our study for both contraceptive methods are those commonly associated with progestin-only contraceptive use.…”
Section: Figuresupporting
confidence: 57%
See 1 more Smart Citation
“…There was a significant decrease in the recurrence rate of dysmenorrhea (P¼ .019) and significant reduction in the mean dysmenorrhea VAS score when compared with non-users. Additionally, a significant improvement in the VAS pain score (baseline 4.26 vs. 0.50, P< .0001) was reported among 28 patients after laparoscopic surgery for endometriosis followed up for 3 years after placement of the LNG-IUS (26). The bleeding patterns reported in our study for both contraceptive methods are those commonly associated with progestin-only contraceptive use.…”
Section: Figuresupporting
confidence: 57%
“…Two studies have evaluated the long-term effectiveness of the LNG-IUS in patients with endometriosis-associated pelvic pain (25,26). Other authors (25) assessed the LNG-IUS for up to 30 months after insertion following surgical excision of endometriotic lesions and endometriomas.…”
Section: Figurementioning
confidence: 99%
“…There is no consensus regarding whether the levonorgestrel-releasing intrauterine device could reduce the recurrence rate either. [ 19 20 ] Our study showed that postoperative medication was not an independent risk factor for ovarian EM in patients aged 45 years and over, nor did it affect the recurrence in patients who underwent ovarian preservation surgery.…”
Section: Discussionmentioning
confidence: 74%
“…Previously Vercellini et al [24] had published a pilot study using LNG-IUD versus expectant management after CS for symptomatic endometriosis with signi cant reduction of dysmenorrhea and risk of recurrence. Subsequently, other studies [9,[25][26][27][28][29][30][31][32] have also shown that LNG-IUD is an effective and well accepted treatment to reduce dyspareunia and dysmenorrhea and increase quality of life in women with suspected endometriosis. However, the long-term maintenance therapy using LNG-IUD after surgery was not effective for preventing endometrioma recurrence [30].…”
Section: Discussionmentioning
confidence: 99%